Differences by transplant type in stool multiplex PCR testing for acute diarrhea in post-solid organ transplantation - Verma, Abhishek; Hine, Ashley M.; Joelson, Andrew; Mei, Rena; Lebwohl, Benjamin; Axelrad, Jordan E. (Frontiers in Gastroenterology, 2022)
Background Diarrhea in solid organ transplant (SOT) recipients is common, morbid, and increasingly evaluated using multiplex gastrointestinal PCR panel (GI panel) testing. We aimed to characterize differences between transplant organ types in GI panel evaluation of acute diarrhea in SOT recipients. Methods We performed a dual-center retrospective cross-sectional study of adult SOT recipients with acute diarrhea who underwent GI panel testing. Demographic, transplant, testing context, and GI panel data were collected. Patients were stratified by transplant type. The primary outcome was a positive GI panel. Results Of 300 transplant recipients (58 heart, 65 liver, 68 lung, and 109 renal), 118 had a positive GI panel. Renal transplant status correlated with more frequently positive GI panel and less frequent hospitalization. In a multivariate analysis adjusting for demographic factors, hospitalization, immunosuppression, and transplant age, renal transplantation was independently associated with a positive GI panel compared to lung transplantation (aOR 2.98, 95% CI 1.27-7.16). Older transplant age and outpatient testing were also independently associated with a positive GI panel. The GI panel result was associated with changes to antibiotic management. Conclusions In the evaluation of SOT recipients with acute diarrhea, GI panel result varies by transplant type, transplant age, and testing location and may affect subsequent antimicrobial therapy.